Case Report: Disseminated herpes simplex virus complicated by hemophagocytic lymphohistiocytosis in a neonate - Nicholas Tadros; Nihal Godiwala (Frontiers in Pediatrics)
Neonatal herpes simplex virus (HSV) infection carries a high mortality rate due to its potential to cause disseminated disease involving multiple organ systems, which can rapidly progress to shock and death if not promptly treated. In rare cases, neonates may mount an uncontrolled inflammatory response leading to hemophagocytic lymphohistiocytosis (HLH), a severe hyperinflammatory syndrome. We present a case of neonatal HSV infection complicated by HLH, highlighting the challenges of managing both conditions concurrently. Our therapeutic approach demonstrated a reduction in systemic inflammation and viral load; however, despite these efforts, the patient developed multiorgan failure and ultimately died from the initial disease process. This case underscores the severity of neonatal HSV infection and emphasizes the critical role pediatricians play in early identification of transmission risk factors and prevention strategies.